2012
DOI: 10.1177/0363546512461903
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes of Postoperative Septic Arthritis After Anterior Cruciate Ligament Reconstruction

Abstract: Patients who develop septic arthritis as a complication of ACL reconstruction surgery have diminished long-term subjective, functional, and radiographic outcomes compared with historical reports of uncomplicated cases, likely related to pain from advanced arthritis. As compared with their own earlier follow-up, these patients had declines in pain-related subjective measures but remained stable or improved in both functional testing and activity-related subjective scales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…55 At a mean 17.9-year follow-up (range, 17.1-18.6 years), each patient had a decline in SF-36, Lysholm, and IKDC scores and increase in KT-1000 arthrometer displacement. Radiographic and MRI studies showed progression of arthritis in all patients as compared with their 36-month follow-up.…”
Section: Outcomes After Infectionmentioning
confidence: 96%
See 1 more Smart Citation
“…55 At a mean 17.9-year follow-up (range, 17.1-18.6 years), each patient had a decline in SF-36, Lysholm, and IKDC scores and increase in KT-1000 arthrometer displacement. Radiographic and MRI studies showed progression of arthritis in all patients as compared with their 36-month follow-up.…”
Section: Outcomes After Infectionmentioning
confidence: 96%
“…In contrast, clinical outcomes inferior to control subjects without infection appeared to be secondary to articular cartilage degeneration. 55 Four infections with the most significant functional limitations had severe bicondylar focal articular surface irregularities noted using magnetic resonance imaging (MRI) upon final follow-up at a mean of 36 months (range, 28-42 months). These patients averaged 12.25 days of inpatient hospital stay for these infections.…”
Section: Outcomes After Infectionmentioning
confidence: 99%
“…In most series, however, continuous passive motion was initiated in days following debridement, and weight bearing was not initially allowed. While in some series weight bearing was allowed when wounds were clinically healed [19], other series waited until the sixth post-operative week [11,37]. Our recommendation is to initiate in the firsts post-operative days a graded knee-strengthening programme including quadriceps and hamstrings strength through progressive isometric, isotonic and isokinetic exercises.…”
Section: Diagnosismentioning
confidence: 99%
“…Shub et al [37] published a study with four cases of infections following ACLR with a mean follow-up of 17.9 years and reported that patients had diminished subjective, functional and radiographic outcomes compared with uncomplicated cases. Compared with an earlier functional follow-up, those patients improved in terms of pain and remained stable in terms of both functional scoring and activity-related subjective scales.…”
Section: Functional Outcomesmentioning
confidence: 99%
“…11 " 1517-23 ' 26 While there are no defined healthcare-associated infections, including surgical site infectreatment guidelines, typical treatment of ACL reconstructions (SSIs). The accuracy of International Classification of tion-related infection includes antibiotics and arthroscopic Diseases, Ninth Revision, Clinical Modification or open drainage of the knee.…”
mentioning
confidence: 99%